Serum levels of TIMP-1 and MMP-7 as potential biomarkers in patients with metastatic colorectal cancer - Vočka, Michal; Langer, Daniel; Fryba, Vladimir; Petrtyl, Jaromir; Hanus, Tomas; Kalousova, Marta; Zima, Tomas; Petruzelka, Lubos (The International Journal of Biological Markers, 2019)
OBJECTIVE: Tissue inhibitor of metalloproteinases 1 (TIMP-1) and matrix metalloproteinase 7 (MMP-7) were reported to have potent growth promoting activity. Lack of balance between MMPs and TIMPs is an important factor in the development of gastrointestinal malignancies. METHODS: We collected serum samples from 97 patients with metastatic colorectal cancer and 79 samples from healthy controls. Serum levels of TIMP-1 and MMP-7 were measured immunochemically and compared with standard tumor markers carcinoembryonic antigen and CA19-9. RESULTS: Serum levels of TIMP-1 and MMP-7 were significantly higher in patients with colorectal cancer compared to healthy controls (both, P < 0.001). TIMP-1 and MMP-7 correlate with the presence of colon involvement (P = 0.001; P = 0.012) and the presence of liver metastases (P = 0.002; P = 0.037), and negatively correlate with pulmonary metastases (P = 0.014; P = 0.005). MMP-7 had similar sensitivity and the same specificity as carcinoembryonic antigen. TIMP-1 and MMP-7 had better sensitivity than CA19-9. TIMP-1 and MMP-7 level correlate with worse outcome (P = 0.002). CONCLUSION: The results indicate that TIMP-1 and MMP-7 are effective biomarkers in patients with metastatic colorectal cancer with good sensitivity. TIMP-1 and MMP-7 levels strongly correlate with the extent of liver disease and have prognostic value.
Keywords: metastázy nádorů; Matrix Metalloproteinase 7; Biomarkers, Tumor; Middle Aged; Colorectal Neoplasms; mužské pohlaví; Neoplasm Metastasis; ženské pohlaví; nádorové biomarkery; tkáňový inhibitor metaloproteinasy 1; Tissue Inhibitor of Metalloproteinase-1; Humans; matrixová metaloproteinasa 7; Female; kolorektální nádory; lidé; Male; lidé středního věku